2023
DOI: 10.1007/s10709-023-00184-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation of the WRKY transcription factor gene family in weeping forsythia: expression profile and cold and drought stress responses

Abstract: Weeping forsythia is a wide-spread shrub in China with important ornamental, medicinal and ecological values. It is widely distributed in China's warm temperate zone. In plants, WRKY transcription factors play important regulatory roles in seed germination, flower development, fruit ripening and coloring, and biotic and abiotic stress response. To date, WRKY transcription factors have not been systematically studied in weeping forsythia. In this study, we identified 79 WRKY genes in weeping forsythia and class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The drought tolerance of NAC TFs has been demonstrated in various crops, such as rice [ 31 ] and soybean [ 32 ]. Yang et al found 13 WRKY genes involved in drought response in the study of weeping forsythia, most of which responded to drought stress by regulating the abscisic acid signaling pathway [ 33 ]. GmERF113 downregulates abscisic acid 8′-hydroxylase and upregulates various drought-related genes, which improves drought resistance and affects the ABA content in soybean [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drought tolerance of NAC TFs has been demonstrated in various crops, such as rice [ 31 ] and soybean [ 32 ]. Yang et al found 13 WRKY genes involved in drought response in the study of weeping forsythia, most of which responded to drought stress by regulating the abscisic acid signaling pathway [ 33 ]. GmERF113 downregulates abscisic acid 8′-hydroxylase and upregulates various drought-related genes, which improves drought resistance and affects the ABA content in soybean [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these stressors, drought stands out as particularly critical due to its frequent occurrence, prolonged duration, and wide-ranging impact. In response to stress signals such as drought, high salinity, and cold, plants activate specific functional genes through signal transduction processes [1]. Finally, these gene products prompt adaptive physiological and biochemical responses, facilitating plant survival [2].…”
Section: Introductionmentioning
confidence: 99%